Pressure Sensor Stability Analysis of Positive End Expiratory Pressure Parameters in Flow Analyzer Design - Wakidi, Levana Forra; Irianto, Bambang Guruh; Kholiq, Abd.; Prasetyo, Eko Dedi; P, Chandrasekaran (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The Positive End Expiratory Pressure (PEEP) parameter is a parameter that must be considered in the process of determining the patient's condition, a safe threshold, and must be in accordance with the settings. However, the PEEP value on the ventilator often does not match the settings so that the measuring instrument capable of detecting PEEP on the ventilator is the Flow Analyzer. The purpose of this study was to design a Flow Analyzer using the MPX2010 sensor to analyze the stability of the PEEP parameters on the ventilator. The main contribution of this research is the design of a simple Flow Analyzer device with stable monitoring of PEEP parameters and the availability of many required setting options. This study used PEEP settings of 0, 5, 8, 11, 14, 17, 20, 23, 26, and 29 cmH2O. In this case, data were collected using a ventilator with VCV (Volume Control Ventilation) and PCV (Pressure Control Ventilation) modes. The tool used for reference from standard measurements was the Standard Flow Analyzer tool. The results of this study indicated that the measurement accuracy of PEEP parameters with the Flow Analyzer module at each PEEP setting had the smallest error of ±0% at 0 cmH2O setting so that it also had the smallest value of 0 by standard. deviation and uncertainty (UA) value 0 at each setting. Meanwhile, the Flow Analyzer measurement module had the largest error in the 5 cmH2O setting, which was ±13.2% with the largest correction value of 0.77. Based on the data obtained, the monitoring of the PEEP parameter was considered quite stable even though the value was still out of tolerance. Therefore, the monitoring of PEEP stability parameters can be implemented during the ventilator calibration process in order to analyze damage and reduce the time of damage to the ventilator.